Two-Tier Bargaining - Tito Boeri (Institute for the Study of Labor (IZA), 2014)
Two-tier bargaining structures, in which plant-level wage negotiations supplement industry-level wage setting, are present in a number of EU countries, as unions resist pressures for greater decentralization in wage determination. In principle, these two-tier structures could reconcile macroeconomic stability with a closer link between productivity and pay. Evidence from an ECB firm-level survey suggests, however, that two-tier regimes may end up getting the worst of either fully centralized and fully decentralized systems, as they do not allow incentive schemes to operate downwards, reduce the participation of firms to collective bargaining, and do not seem to improve either microeconomic and macroeconomic adjustment to shocks.
Keywords: J31; J33; J51; 330; wage drift; favourability principle; productivity-related pay